Analysis Categories of Verb Semantic In Prince William’s Oath of Loyalty at the King’s Coronation - Putri, Amelia Amanda; Amalia, Karina Dea; Triana, Dwi; Yasmin, Zarah Khodijah; Lubis, Hanny Shah Rahma Reswara (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2023)
This paper aims to describe the categories and semantic roles of verbs in Prince William's oath of allegiance during the coronation of King Charles III. The paper employs a qualitative approach. The researchers used documentation techniques to gather data by reading or watching various data sources from YouTube and media articles, and taking note of the required data. Data analysis was conducted using analytical techniques. Based on the data analysis, the following results were obtained. First, the researchers identified the semantic categories of verbs in Prince William's oath of allegiance at King Charles III's coronation. The verb categories are 'pledge' and 'bear'. Second, the verb "pledge" belongs to the category of action verbs. Additionally, the verb "bear" also belongs to the category of action verbs.